SKETCHING THE SEMANTIC CHANGE OF JAHANAM AND HIJRAH: A CORPUS BASED APPROACH TO MANUSCRIPTS OF ARABIC-INDONESIAN LEXICON - Puspita, Dewi; Yusuf, Kamal (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
There are a significant number of lexical borrowings from Arabic language to Indonesian language. Among of them are the words jahanam and hijrah. These words are diachronically can be traced and found in literatures and religious texts. This paper seeks to scrutinize the semantic change of jahanam and hijrah. This paper analyses jahanam and hijrah as they are used in both old manuscripts and modern texts. To see their semantic change behaviour, collocation and concordance of their contexts were analysed. The manuscripts employed as the source of research data were taken from the Malay Concordance Project (MCP) which comprises of 165 classical Malay literatures containing some Islamic texts, Corpora Collection Leipzig University, and WebCorp Live Birmingham City University. Using the corpus linguistics method, this research manages to demonstrate how words change semantically through time. The results of this study can be used as material for the preparation of the Indonesian-Arabic etymology dictionary.